2019
DOI: 10.1017/s0033291718004166
|View full text |Cite
|
Sign up to set email alerts
|

CBT for schizophrenia: a critical viewpoint

Abstract: In England and Wales, cognitive behavioral therapy (cognitive therapy, CBT) has been part of official treatment guidelines for schizophrenia since 2002 (NICE, 2009, p. 212). The 2014 NICE guideline (NICE, 2014), which is based on the same meta-analytic evidence as its predecessor in 2009, recommends that it be offered to all people with schizophrenia, including first-episode patients and those with established illness, and to patients who are actively symptomatic and in remission. Similar recommendations are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…The largest meta‐analysis reported a small SMD in comparison with TAU (0.33, see Figure 2) 111 . Considering all meta‐analyses, small effect sizes compared to nonspecific controls were found for overall symptoms, positive and negative symptoms (SMDs: 0.32, 0.24 and 0.08, respectively) 138 . In comparison to TAU, psychotherapy achieved small to medium SMDs for negative symptoms (0.15‐0.58) 110,112 .…”
Section: Resultsmentioning
confidence: 95%
“…The largest meta‐analysis reported a small SMD in comparison with TAU (0.33, see Figure 2) 111 . Considering all meta‐analyses, small effect sizes compared to nonspecific controls were found for overall symptoms, positive and negative symptoms (SMDs: 0.32, 0.24 and 0.08, respectively) 138 . In comparison to TAU, psychotherapy achieved small to medium SMDs for negative symptoms (0.15‐0.58) 110,112 .…”
Section: Resultsmentioning
confidence: 95%
“…In addition to medication, cognitive behavioural therapy (CBT), a non‐pharmacological treatment, has been used to treat psychosis for patients with schizophrenia (NICE, 2014). However, a review study found limited effects of conventional CBT on reducing psychotic symptoms (Jauhar et al., 2019). In recent years, mindfulness‐based intervention, a novel branch of CBT, was developed for patients with schizophrenia (Cramer et al., 2016; Louise et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that conventional cognitive behavioural therapy (CBT) aiming to manage the cognitive distortions only led to small‐to‐moderate reductions in psychotic symptoms (Jauhar et al., 2019; Naeem et al., 2016). However, high dropout rates from conventional CBT suggest low clinical feasibility of this treatment modality (Bighelli et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…115–118). Although there is a certain amount of controversy regarding its effectiveness in the treatment of schizophrenia [ 21 ], on the whole, research yields positive results, especially in the decrease of positive symptoms [ 22 , 23 , 24 ]. A crucial difference between CBT and MBIs is that the latter do not focus the intervention on the psychotic symptoms per se but rather on the relationship patients establish with psychotic-like experiences.…”
Section: Introductionmentioning
confidence: 99%